PHYLOGENETIC ANALYSIS OF FUSARIUM OXYSPORUMF STRAINS ISOLATED FROM STRAWBERRY CROPSFRAGARIA ANANASSADUCH IN THE PROVINCE OF PICHINCHA (ECUADOR) - L., ANGELICA TIGRE; ERAZO, FREDY; YANEZ, DANILO; BAYAS-MOREJON, FAVIAN (International Journal of Current Pharmaceutical Research, 2020)
Objective: Strawberry cultivation has acquired great importance for consumption, promoting the increase of its production in Ecuador. However, the process of importing plant material from producing countries in order to improve domestic production has contributed to the dissemination of the fungus Fusarium oxysporum f. sp. fragariae. To identify the presence of the pathogen, by applying molecular techniques to the Fusarium strains isolated from strawberry crops. Methods: Nine two diseased strawberry plants and 92 asymptomatic plants were analyzed. From these samples, 13 fungi with the characteristics of the Fusarium genus were identified. The isolates were analyzed at the molecular level, by PCR (Polymerase chain reaction) amplifying the ITS regions of the rDNA and the EF-1α region. Results: The PCR product was sequenced to elucidate the phylogenetic relationships between the isolates, identifying 12 strains as F. oxysporum f. sp. fragariae. These results confirmed the presence of the fungus in the strawberry crops analyzed, representing a contribution to the search for control alternatives to avoid the spread of the pathogen. Conclusion: The PCR product was sequenced to elucidate the phylogenetic relationships between the isolates, identifying 12 strains as F. oxysporum f. sp. fragariae.